2017
DOI: 10.4103/pm.pm_368_16
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition of Moringa oleifera ethyl acetate fraction and its biological activity in diabetic human dermal fibroblasts

Abstract: Background:Moringa oleifera (MO), commonly known as the drumstick tree, is used in folklore medicine for the treatment of skin disease.Objective:The objective of this study is to evaluate the ethyl acetate (EtOAc) fraction of MO leaves for in vitro antibacterial, antioxidant, and wound healing activities and conduct gas chromatography-mass spectrometry (GC-MS) analysis.Materials and Methods:Antibacterial activity was evaluated against six Gram-positive bacteria and 10 Gram-negative bacteria by disc diffusion m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…18 The M. oleifera leaves ethanol extract (MOLE), with its flavonoid compounds, is a novel candidate for skin wound healing with minimum side effects. 19 The gross wound size (Figure 1) significantly reduced after oral MOLE administration and was accompanied by a dose-dependent wound area reduction (Figure 2). This was in line with a previous study, where topical MOLE accelerated excisional wound healing in diabetic rats by reducing wound size, increasing wound contraction and tissue regeneration, downregulating inflammatory mediators, antibacterial activity, and regulating VEGF angiogenic markers.…”
Section: Discussionmentioning
confidence: 96%
“…18 The M. oleifera leaves ethanol extract (MOLE), with its flavonoid compounds, is a novel candidate for skin wound healing with minimum side effects. 19 The gross wound size (Figure 1) significantly reduced after oral MOLE administration and was accompanied by a dose-dependent wound area reduction (Figure 2). This was in line with a previous study, where topical MOLE accelerated excisional wound healing in diabetic rats by reducing wound size, increasing wound contraction and tissue regeneration, downregulating inflammatory mediators, antibacterial activity, and regulating VEGF angiogenic markers.…”
Section: Discussionmentioning
confidence: 96%
“…The scavenging activity increased in a concentration-dependent manner due to the scavenging capacity of the fraction and was comparable to quercetin. The IC50 value signifies the concentration required to scavenge 50% of the initial DPPH radicals (Gothai et al, 2017). The quercetin compound has the smallest IC50 value of 10.76 ppm with the highest antioxidant activity because this compound is a pure flavonoid compound with the maximum free radical scavenging.…”
Section: Discussionmentioning
confidence: 99%
“…Research showed that Moringa leaves contain quercetin, carotenoid, amino acids and alkaloids, as well as a combination of phenolic compounds (Gupta et al, 2015;Karthivashan et al, 2015). The antioxidant activity of ethanolic extract Moringa leaf is IC50 22.18 ppm Rizkayanti et al, (2017) while the ethyl acetate fraction was 18.21 ± 0.06 ppm (Gothai et al, 2017). The quercetin content of Moringa leaves has antioxidant activity, so it is necessary to study its effectiveness in regenerating skin cells topicall (Almeida et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Phenolic compounds in the M. oleifera leaves EtOAc fraction have antioxidant activity that acts as hydrogen donors or reducing agents, which improves regeneration and organization of the new tissue in wound healing. 53 Moringa flowers and seeds also have antioxidant and anti-inflammatory activities due to their compounds such as ascorbic acid, carotenoids, tannins, alkaloids, glycosides, flavonoids and phenolic compounds kaempferol, quercetin, and the unique combination of fatty acids in the flower extract. 38,54 In an in vitro study, a combination of M. oleifera and Aloe vera containing quercetin to treat wounds, showed the highest anti-inflammatory effect and quercetin treatment with higher phenolic content was a modality with higher anti-inflammatory activity.…”
Section: Moringa Oleifera Compounds In Promoting Wound Healing Processmentioning
confidence: 99%
“…The M. oleifera ethyl acetate fraction supported the wound healing activity by promoting the proliferation and migration of fibroblast cells and neovascularization. 53 Moringa oleifera contains amino acids, fatty acids, vitamins, and trace elements that are all important in cellmediated immune responses. Fatty acids, vitamin D, and trace elements that not only facilitate the proliferation and maturation of neutrophils, but also the secretion of cytokines that enhance neutrophil migration and adhesion.…”
Section: Effect Of M Oleifera Extract On Chronic Woundsmentioning
confidence: 99%